Myasthenia gravis with ocular symptoms following a ChAdOx1 nCoV-19 vaccination: A case report - Min Chae Kang; Kyung-Ah Park; Ju-Hong Min; Sei Yeul Oh (American Journal of Ophthalmology Case Reports, 2022)
Purpose: We report on the case of a 35-year-old man who developed myasthenia gravis with ocular symptoms following a ChAdOx1 nCoV-19 vaccine injection. Observations: A 35-year-old man complained of binocular diplopia one month following ChAdOx1 nCoV-19 vaccination. He had weak infraduction of the left eye. Upper and lower extremity strength was normal on presentation. A serum antiacetylcholine receptor antibody titer was elevated at 1.60 nmol/L. His diplopia improved temporarily following the application of an ice pack for 2 min. Conclusions and importance: This case report describes a rare occurrence of myasthenia gravis with ocular symptoms as a potential complication of ChAdOx1 nCoV-19 vaccination.